Analysis of electro-hydrostatic actuator in more electric aircraft. - Francival Barbosa Júnior (2006)
The aim of this dissertation is to evaluate the possibility of using electrically powered systems instead of a centralized hydraulic system composed of set of distribution pipes for aircrafts' primary control surfaces actuation. Focus will be given in the following topics: Description of new actuation technologies; Option chosen to be studied among the new possibilities; Comparison between the traditional system and the new proposal e System engineering evaluation regarding: weight, safety, thermal issue, connection with electric system, maintenance and certification. Besides that, a more electric actuation architecture will be proposed and compared with the conventional option for an airplane design's case study. A simulation model will be developed to describe the more electric actuator behavior and preview its interaction with other systems. This model will be included in a closed loop to command a primary surface. The closed-loop project will be developed based on an algorithmic method. A Genetic Algorithm (GA) will be implemented to define the gains. Finally, the results obtained will be discussed.